From Colonial Spanish to Modern Nahuatl: A Study of Neologisms and Lexical Exchange (BEOIBERISTIKA - Časopis za iberijske, latinoameričke i komparativne studije (ISSN: 2560-4163 Online), 2025)
The article examines the linguistic interaction between Spanish and Nahuatl over several centuries, with particular emphasis on mutual lexical influence. The first part analyzes how Nahuatl enriched the Spanish spoken in Mexico since the beginning of colonization, focusing on the incorporation of Nahuatl loanwords into Castilian and the lexical strategies used by conquistadors, colonizers, and missionaries to name aspects of the Mesoamerican world previously unknown to Europeans. The second part shifts focus to contemporary Nahuatl, highlighting the influence of Spanish and the mechanisms Nahuatl speakers employ to create neologisms in response to the demands of modern life, especially in the fields of technology and computing. The study emphasizes the creativity of Nahuatl speakers and their ability to adapt their language to new contexts, which serves as both an expression of cultural resilience and a means of ensuring the vitality and continuity of Nahuatl in the present.
Keywords: neologism; word formation; linguistic interference; Nahuatl loanwords